KONTRIBUSI MANAJEMEN PENGELOLAAN ZAKAT PRODUKTIF DALAM MENGANTISIPASI ANCAMAN RESESI EKONOMI GLOBAL - Naufal, Yamani; Dian May Syifa; Muhammad Alfiqtrah Aslam (Mitsaqan Ghalizan, 2025)
Economic recession is a condition of declining global economic growth that has the potential to weaken a country's stability and affect the domestic economy at large. Amid this threat, Islamic economics offers a system that aims to ensure socio-economic justice through Islamic philanthropic instruments, namely Zakat, Infaq, Sedekah, and Wakaf (ZISWAF). This study aims to analyze the contribution of productive zakat and the urgency of applying modern management in its administration as a strategic strategy to anticipate the impact of global recession. The method used in this study is qualitative with a library research type and a conceptual approach. The results of the discussion show a significant difference between consumptive zakat and productive zakat. Consumptive zakat is short-term in nature and is used to fulfill basic needs. In contrast, productive zakat is oriented towards long-term empowerment through the provision of business capital, which is expected to have a multiplier effect. This mechanism aims to improve the standard of living of mustahiq (zakat recipients) so that they become economically independent and transform into muzakki (zakat givers) in the future. This transformation will encourage increased consumption and economic scale, creating economic growth accompanied by equality. In addition, managing institutions such as the Zakat Management Agency (BAZ) must apply the principles of transparency and accountability by publishing financial reports to the public in order to gain public trust.